2017
DOI: 10.1213/ane.0000000000001622
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Intravenous Remifentanil Use for Labor Analgesia at Academic Medical Centers in the United States

Abstract: Remifentanil is most commonly offered when neuraxial labor analgesia is contraindicated. There is no consensus regarding the optimal administration, dosing strategy, or requirements for maternal monitoring, which may pose a patient safety issue. This exploratory survey evaluated the current practices regarding remifentanil use for labor analgesia at academic centers in the United States. Of 126 obstetric anesthesia directors surveyed, 84 (67%) responded. In 2014 to 2015, an estimated 36% (95% confidence interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…Fetal drug exposure in later trimesters may also lead to complications, as drugs may interfere with fetal growth or result in the acute interference of key homeostatic processes in the unborn child. Examples include intra‐uterine exposure to opioid analgesics, resulting in postpartum withdrawal symptoms and respiratory depression in the newborn . There are also cases in which maternal drug treatment is prescribed to treat or prevent disease in the unborn child.…”
Section: Current Status and Need For Clinical Studies In Pregnant Womenmentioning
confidence: 99%
“…Fetal drug exposure in later trimesters may also lead to complications, as drugs may interfere with fetal growth or result in the acute interference of key homeostatic processes in the unborn child. Examples include intra‐uterine exposure to opioid analgesics, resulting in postpartum withdrawal symptoms and respiratory depression in the newborn . There are also cases in which maternal drug treatment is prescribed to treat or prevent disease in the unborn child.…”
Section: Current Status and Need For Clinical Studies In Pregnant Womenmentioning
confidence: 99%
“…A survey from the USA gives a hint that the contrary might be the case. The authors found that ‘ No complications occurred in the four centres that reported using remifentanil more than 10 times in the previous year ’, while a total of nine patients with respiratory depression were reported in centres that did not have routine experience with the method . Standard protocols were lacking, and no information was provided on whether staffs were trained.…”
Section: Confusing Recommendationsmentioning
confidence: 99%
“…We believe that the role of vigilant manual monitoring could be further augmented by an interactive technology with safety thresholds to improve the safety of mother and fetus. We would like to add to the recent correspondence about preventing wrong site blocks [1][2][3]. In Sandwell and West Birmingham Hospitals NHS Trust, we have developed two adhesive stickers to overcome this problem.…”
Section: F Weinigermentioning
confidence: 99%
“…During remifentanil administration in labouring women, hypoxia typically occurs late in the apnoea sequence, and usually after the respiratory rate and end-tidal carbon dioxide have alerted to impending or actual apnoea [2]. Therefore, we are concerned that the vital signs used in the VPIA drug-delivery system may trigger cessation of drug delivery after an apnoea has occurred, when the progression towards respiratory and possibly cardiac arrest [3] may have already irreversibly occurred.…”
mentioning
confidence: 99%
See 1 more Smart Citation